WEBBING TECHNIQUE TO IMPROVE THE STUDENTS´ WRITING RECOUNT - Ariana Ariana (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2015)
This research was aimed at investigating the use of webbing technique in teaching writing recount text.  A  quasi  experimental  design  was  employed  with  two  classes  of  the  eleventh  graders  at  one  school  in  Sungguminasa, Gowa  selected  with cluster sampling  as  sample.  The  data  were  obtained  through  a  pre-test,  a  post-test  and  an  questionnaire.  The writing assessment was covering content, schematic structure, and language use.  The findings were analyzed statistically using independent t-test procedure.   The statistical computation showed that webbing technique was likely effective in  improving  the  students’  writing  skill  in  recount text  (value of t  6,74value of t table1,99). Furthermore, the students´ perception towards webbing technique is 91,7% students agree that this technique could help them to increase their writing skill. Designing  the  learning  purpose  appropriately  which  considers  students’  needs  and  language  level  may  ease  teachers  to  use  the webbing technique  in  improving  students’  writing recount text.  The  teachers  may  try  to  take  advantage  of  webbing technique  to  be  utilized  in  their  classroom  activities  to  conduct  an  effective  and  interesting  learning atmosphere in the classroom.